The Effect of the Hardener on the Characteristics of the Polyester-Based Coating - Irina N. Vikhareva (Engineering Proceedings)
In order to reduce negative technological factors when using epoxy resin as a thermosetting binder for the composition, a less viscous epoxyamine resin was studied. To impart elastic properties, the resin was modified with two components: polyester based on sebacic acid and a polyamide hardener. The compositions were cured under various temperature conditions: without heating and with maximum heating at a temperature of 120 °C. The formation of a crosslinked polymer using the IR spectrum is shown. The influence of temperature conditions on the degree of curing of polymer films was determined: the largest amount of gel fraction was formed with gradual heating of the mixture. However, the best physical, mechanical, and operational characteristics were obtained for the sample, which was cured at maximum temperature.